Genomics with Care : Minding the Double Binds of Science - Fortun, Michael (Book collections on Project MUSE., 2023)
"Genomics with Care is an experimental ethnography of contemporary genomics research. Mike Fortun offers a way of analyzing science as an amalgam of thought and affect, formal method and tacit knowledge, algorithms and ethics. The book privileges the concept of care within science and, in doing so, draws on recent feminist scholarship in anthropology, philosophy, and science studies. Fortun explores the sometimes pathological, sometimes creative, and always paradoxical nature of the double binds of science and care. He conceptualizes four different modes of care in science: curation, scrupulousness, solicitude, and friendship. He approaches these concepts through the book's dominant method of what he terms 'ethnogrammatology': a combined ethnographic and deconstructive reading. The book is written in the spirit of experimental ethnography to convey how the sciences, and the doing of science, is a matter of the tight, intimate, but uneasy relationship between thinking, caring, and affect"--